2020
DOI: 10.3389/fped.2020.00120
|View full text |Cite
|
Sign up to set email alerts
|

The Risk of Developing Constipation After Neonatal Necrotizing Enterocolitis

Abstract: Background: Neonatal necrotizing enterocolitis (NEC) is a complex and lethal inflammatory bowel necrosis that primarily affects premature infants. Gut dysbiosis has been implicated in the pathogenesis of NEC. We aim to assess the association between NEC and two other diseases in children, including allergic diseases and constipation, considered to be associated with the alterations in gut microbiota composition. Methods: This retrospective population-based cohort study was conducted using the Taiwan Birth Regi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…It has been reported that children with functional constipation are more likely to be born by C-section or to have a shorter duration of breastfeeding, suggesting that early gut microbiome events may increase the risk of developing functional constipation later in life (26). For instance, children with a history of necrotizing enterocolitis, who are often premature and treated with prolonged courses of antibiotics, have a higher incidence of functional constipation than healthy children (27). Infant S011 was born vaginally and was solely breastfed during the period in which constipation was reported.…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that children with functional constipation are more likely to be born by C-section or to have a shorter duration of breastfeeding, suggesting that early gut microbiome events may increase the risk of developing functional constipation later in life (26). For instance, children with a history of necrotizing enterocolitis, who are often premature and treated with prolonged courses of antibiotics, have a higher incidence of functional constipation than healthy children (27). Infant S011 was born vaginally and was solely breastfed during the period in which constipation was reported.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the accuracy of the medical codes may have affected the validity of the data. To minimize diagnostic miscoding errors, we only recruited patients with at least one inpatient claim or two outpatient claims for ADPKD and related complications at least 30 days after the index date of ADPKD diagnosis 36 . However, the true incidence and complication rates of ADPKD may have been underestimated because of our strict inclusion criteria or patients not seeking medical care.…”
Section: Discussionmentioning
confidence: 99%
“…One study suggests that constipation in low birth weight infants is associated with neurological developmental disorders and may also be a secondary consequence of neonatal ischemic conditions such as necrotizing enterocolitis (Cunningham et al, 1998). Research by Shan-Ming Chen, et al also stated that constipation is associated with NEC (Chen et al, 2020).…”
Section: Discussionmentioning
confidence: 99%